A comparison of the molecular organization of genomic regions associated with resistance to common bacterial blight in two Phaseolus vulgaris genotypes - Perry, Gregory E.; DiNatale, Claudia; Xie, Weilong; Shi, Chun; Navabi, Alireza; Reinprecht, Yarmilla; Crosby, William C.; Yu, Kangfu; Pauls, K. Peter (Frontiers in Plant Science, 2013)
Resistance to common bacterial blight, caused by Xanthomonas axonopodis pv. phaseoli, in Phaseolus vulgaris is conditioned by several loci on different chromosomes. Previous studies with OAC-Rex, a CBB-resistant, white bean variety of Mesoamerican origin, identified two resistance loci associated with the molecular markers Pv-CTT001 and SU91, on chromosome 4 and 8, respectively. Resistance to CBB is assumed to be derived from an interspecific cross with Phaseolus acutifolius in the pedigree of OAC-Rex. Our current whole genome sequencing effort with OAC-Rex provided the opportunity to compare its genome in the regions associated with CBB resistance with the v1.0 release of the P. vulgaris line G19833, which is a large seeded bean of Andean origin, and (assumed to be) CBB susceptible.. In addition, the genomic regions containing SAP6, a marker associated with P. vulgaris-derived CBB-resistance on chromosome 10, were compared. These analyses indicated that gene content was highly conserved between G19833 and OAC-Rex across the regions examined (>80%). However, fifty-nine genes unique to OAC Rex were identified, with resistance gene homologues making up the largest category (10 genes identified). Two unique genes in OAC-Rex located within the SU91 resistance QTL have homology to P. acutifolius ESTs and may be potential sources of CBB resistance. As the genomic sequence assembly of OAC-Rex is completed, we expect that further comparisons between it and the G19833 genome will lead to a greater understanding of CBB resistance in bean.